Social media usage and creativity in Jordan: Knowledge management as a mediator - Hailat, Khaled Qassem; Sawalha, Sumaia Shamsi (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study is to investigate the impact of social media usage on creativity in Jordanian universities, with knowledge management (KM) serving as a mediating factor. A quantitative structured questionnaire was administered to a sample of 1,163 faculty members and administrative staff across various departments. The approach for this research employed a descriptive-analytical method, supported by statistical tools such as descriptive statistics and regression analysis. Results indicate that social media use has a significant direct positive effect on creativity. Moreover, when mediated by KM, the influence of social media on creativity becomes stronger and more stable. KM enhances the ability of institutions to leverage social media for knowledge sharing, collaboration, and idea generation, thus contributing to creative performance. The findings also show that KM alone positively affects creativity, emphasizing its strategic role in academic environments. The study concludes that the combined use of social media and effective KM practices can substantially improve innovation within universities. It recommends that institutions evaluate social media performance more systematically, considering technological, organizational, and environmental factors. Additionally, greater emphasis should be placed on strengthening KM capabilities, enabling decision-makers to foster dynamic, knowledge-driven environments that support continuous improvement and creativity.